(3GdLjT GdYQeQe GdNeGSj aj OhdI ChdGO ehdGfG Ydj GdTQja GdSLdeGSjs - (3eMeO Hf CMeO CcfShS GdbQTj GdShSj CHhYHO Gddg GdhRjQ GdeQGcTj,J (B1294 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdfahS hGdCQhGM dgG HGdCNHGQ GdSGdaI GfHSGW hGSJQhGM gPG hEf ehdGfG s
(3BNQgG (B:s
(3jbhd ehdGfG JHGQc hJYGdi jG EHf BOe dhHdZJ PfhHc YfGf GdSeGA Ke ESJZaQJfj ZaQJ dc Ydi eG cGf efc hdG CHGdj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B19s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B885 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B148 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(43 (3O(B) s
Keywords: (3GdJGQjNs